Pencemaran Logam Berat Terhadap Biota Laut - Sumingkrat Sumingkrat (Jurnal Kimia dan Kemasan, 1999)
The living environment must be managed in order that it may be in harmony with the concept of sustainable development. Heavy metals is one of a toxic materials including on the list a hazardous and toxic waste relation by a Government Regulation. The pollution a heavy metals in the water area increase by industrial activities, where to discharge they waste to the ilegal dumping. Effect accumulation of a heavy metals in the marine biota such as fish, kind of mollusca (anadara sp), etc was absorbed, to caused a hazardous and toxic, that may endanger the environment and the health of human beings.